(untitled) (Bioresearch Communications, 2024)
Sixly two species of anamorphic fungi under 17 genera belonging to the Form family Sphaeropsidaceae and Melanchoniaaece in Bangladesh from 1952 till date are enlisted in this account. The alphabetical checklist of the genera is provided herewith. Further updates will be added in the subsequent versions of the publication. Bioresearch Commu. 10(2): 1495-1500, 2024 (July)